The Effect of Supervision of Pregnant Women in Three Trimester Through the Formation of Lactation Classes on Mothers' Readiness in Providing Exclusive Breastfeeding - Astria, Niki; Siahaan, Gustien; Arista , Devi; Rahmawati , Dwi; Asmajaya, Rudi (Rifa'Institute, 2025)
Introduction: Breast milk is the first food for newborns and is the main nutrition for babies. Self-Readiness is important in breastfeeding, because it is used as a parameter of the mother's ability to breastfeed. Knowledge is one of the factors of the mother's readiness to breastfeed. Objective: The aim of this study was to determine whether there was an influence of health assistance for pregnant women in the third trimester through the formation of lactation classes on the readiness of mothers to provide exclusive breastfeeding with using leaflets and educational videos. Method: This type of research is pre-experimental with the research design used is one group pretest - posttest design. The population in this study were pregnant women in the third trimester in the working area of Kebon Handil Health Center, Jambi City. The sample size in this study was 32 people taken using the total sampling technique. Result and Discussion: he results of the study showed that there was an influence of intervention in providing health assistance through lactation classes regarding lactation management on the level of readiness to breastfeed in pregnant women in the third trimester of the T-test with a p value = 0.0000. Conclusions: it is recommended that Kebon Handil Health Center hold lactation class activities with the material provided being about lactation management as a provision of knowledge for pregnant women in preparing for birth and self-readiness in providing exclusive breastfeeding.